Pengembangan Ekonomi Kreatif Berbasis Industri Rumah Tangga Dalam Meningkatkan Pendapatan Masyarakat : Studi Pada Kelompok Usaha Rumah Tangga Binaan Yayasan EcoNatural Society di Kota Gunungsitoli - Hulu, Fonaha (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2024)
This research aims to explain the development of a creative economy based on home industry carried out by the EcoNatural Society Foundation, explain its impact on people's income, as well as supporting factors in the development of the creative economy at the EcoNatural Society Foundation. The method used is descriptive qualitative research, the method of collecting data is through observation, interviews and documentation of the research object. The data analysis technique uses descriptive analysis. The research results show (1) the development of a creative economy based on home industry carried out by the EcoNatural Society Foundation through the formation of home business groups, (2) an increase in the income of people who participate in home business groups, (3) internal and external factors that become a supporter in the development carried out by the EcoNatural Society Foundation in Gunungsitoli City.